Development Effectiveness of the Paris Declaration: An Empirical Evaluation - Lee, Kye Woo (KDI Journal of Economic Policy, 2013)
This study aims to assess the development effectiveness of the Paris Declaration (2005). Using data collected by the OECD/DAC from 78 developing countries for the period 2005~2010, this study evaluates the role played by the Paris Declaration principles alone and in interaction with aid in promoting per-capita GDP growth. The analysis shows that the overall net impact of aid on promoting economic growth has been negative. However, aid effectiveness has been enhanced by the sound policies or institutions and some Paris Declaration (PD) principles. Of the five principles of the PD, only the alignment and, to some extent, mutual accountability principles of the PD did show a significant and positive role in making aid more effective for economic growth of aid recipient countries. Therefore, OECD’s statement that the PD enhances aid effectiveness is supported only partially. These findings have significant implications for the importance accorded to sound policies and institutions in the growth literature, and for future international development cooperation agenda.